KOMPENSASI DAN PENGHARGAAN SEBAGAI INTERVENING HUBUNGAN ANTARA PENERAPAN DISIPLIN DAN KINERJA PEGAWAI DI BKKBN PROVINSI JAWA TIMUR - Siti Rokhmi Fuadati1; Nuzulianti Rahayu; Hening Widi Oetomo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
The aim of the research is to study and analyze performances of East Java BKKBN’s officers by describing a conceptual framework about both direct and indirect impacts of Disciplinary Applying variables, Compensating, and Rewarding and Performances. In this research, performances levels directly influenced by Disciplinary Applying and indirect by bith disciplinary applying on performances through compensating and rewarding to East Java BKKBN’s officers. Sample of the research was proportionally taken using cluster system and served as respondent were East Java BKKBN’s officers as much 82 people. Data types used in the study were primary and secondary data with the questionnaire division.Based on the performed hypothetical cross-variable causality test using Path Analysis, obtained: Disciplinary Applying variables have a direct impact on performances with value or standardized coeficient of 0.209. Disciplinary Applying variables have an indirect impact on performances through compensating with value or standardized coeficient of 0.066. Disciplinary Applying variables have an indirect impact on performances through rewarding with value or standardized coeficient of 0.323. Disciplinary Applying variables have an indirect impact on performances through compensating and rewarding with value or standardized coeficient of 0.431. More researches are required to develop the goal of this study in the future by observing performance improvement among the officers through Disciplinary Applying and Compensating as well as Rewarding but with different indicator selection than those in the study or adding more variables as well as expanding population thereby such as an analytical framework was obtained.